Operative techniques in thoracic and esophageal surgery - Hawn, Mary T.; Mulholland, Michael W. (Wolters Kluwer, 2015)
This book covers the full range of surgical procedures relating to the trachea, lungs, esophagus, diaphragm, mediastinum, paraesophageal hernias, GERD, esophageal cancer, and esophageal perforation.